Credit Supply and Monetary Policy: Identifying the Bank Balance-Sheet Channel with Loan Applications - Jiménez, Gabriel; Ongena, Steven; Peydró, José-Luis; Saurina, Jesús (American Economic Review, 2012)
We analyze the impact of monetary policy on the supply of bank credit. Monetary policy affects both loan supply and demand, thus making identification a steep challenge. We therefore analyze a novel, supervisory dataset with loan applications from Spain. Accounting for time-varying firm heterogeneity in loan demand, we find that tighter monetary and worse economic conditions substantially reduce loan granting, especially from banks with lower capital or liquidity ratios; responding to applications for the same loan, weak banks are less likely to grant the loan. Finally, firms cannot offset the resultant credit restriction by applying to other banks. (JEL E32, E44, E52, G21, G32)